2018
DOI: 10.1252/jcej.17we149
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Mixing Processes with Complex Fluids

Abstract: The present paper provides an overview of the intensi cation of mixing processes with complex uids. First, mixing processes of rheologically complex uids and their design methodology are discussed. An example of process intensi cation of mixing with rheologically complex uids using a Couette-Taylor ow reactor is introduced. Second, the intensi cation of the mixing of a suspension with high concentration solids and a novel approach for solid-liquid separation using a stirred vessel are discussed. Finally, a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…As an example, low product quality may be resulted by the high gradients in temperature and pH, which are yielded by the poor mixing. The appropriate design of stirrers may allow the good mixing quality, as confirmed by many authors for the agitation of shear-thinning fluids [2][3][4][5].…”
Section: Introductionmentioning
confidence: 85%
“…As an example, low product quality may be resulted by the high gradients in temperature and pH, which are yielded by the poor mixing. The appropriate design of stirrers may allow the good mixing quality, as confirmed by many authors for the agitation of shear-thinning fluids [2][3][4][5].…”
Section: Introductionmentioning
confidence: 85%
“…For example, in order to destroy the cavern, Pakzad et al [4] reported an energy-efficient coaxial mixer for non-Newtonian fluid mixing. However, Ohmura et al [5] noted that cavern formation in the stirred vessel is unavoidable unless excess energy is injected by the impeller to make the fluid circulate through the whole region. Thus, the process design of non-Newtonian fluid mixing needs to be revolutionized to be made sustainable.…”
Section: Introductionmentioning
confidence: 99%